The effect of performing mental exertion during cycling endurance exercise on fatigue indices: sex dependent differences - Amoozi, Hamid; Barzegarpoor, Hamidreza; Rajabi, Hamid; Button, Duane C.; Fayazmilani, Rana (Frontiers in Physiology, 2025)
IntroductionMen and women have different performance abilities, where women have greater tolerance for fatigue in long-distance exercise. Part of this greater tolerance may be due, in part, differences in men’s and women’s mental fatigue capacity during exercise. Thus, the aim of this study was to examine the effect of cycling endurance exercise, along with mental fatigue, on the sex dependent differences in exercise tolerance.MethodsTwenty-five (15 women and 10 men) cyclists in a randomized, controlled, and crossover protocol performed three experimental sessions. In the first session, the cycling peak power output (PPO) was determined and 65% of PPO was used for intensity of the experimental sessions. In sessions 2 and 3, participants performed Cycling + Mental Exertion (ME) (cycling endurance exercise with a ME-stroop task) and Cycling + Movie (cycling endurance exercise while watching a movie). Serum cortisol concentration and a psychomotor vigilance task (PVT) were measured pre‐ and post-sessions. During the experimental sessions rate of perceived exertion (RPE) and heart rate (HR) were recorded every 10 min and participants completed the NASA‐TLX questionnaire directly following the post- PVT.ResultsPerforming Cycling + ME was associated with a longer time to exhaustion (p < 0.05) and higher RPE following 40‐70 min in women than men (p < 0.05). Cycling + ME increased HR following 40-70 min in women (p < 0.05). For both men and women cortisol concentration level was higher pre‐ to post‐Cycling + ME with no difference between sexes. Women exhibited faster reaction times compared to men in both pre‐ and post‐sessions.DiscussionPerforming mental exertion with cycling endurance exercise impairs endurance performance. While our findings align with some previous research, we suggest that men may be more prone to mental fatigue; however, further research needed to confirm this.